THE EFFECTIVENESS OF ROLE-PLAY TOWARDS VOCATIONAL SCHOOL STUDENTS’ SPEAKING SKILL - Bimantara Wicaksana; Enis Fitriani; Munawwir Hadiwijaya (Journey: Journal of English Language and Pedagogy, 2020)
This study aimed at investigating the effectiveness of using role play toward speaking skill in learning English at the Class X students of SMKS Muhammadiyah Pangkalan Bun. Quasi experimental research was administered in this study, using two groups of experimental and control. Multimedia 1 class as the experimental group and Multimedia 2 class as the control group. There were six meetings for each group with four meetings for treatment, and other two meetings for pre-test and post-test. The data were in form of speaking scores emphasizing on fluency, structure, and bravery. From the t-test for independent samples, the result showed that the value of t-test was 0.034 less than 0.05. It means that the result of posttest scores in experimental and control groups are significantly different. Then, from the comparison of the means between pretest and posttest of experimental and control groups, the experimental group’s mean outperformed the control group in 2.20. It means that role play is effective in speaking skill in learning English. Furthermore, this study also showed that role play could create a communicative atmosphere in the classroom.